Effects on Cognitive Functioning of Acute, Subacute and Repeated Exposures to High Altitude - Pun, Matiram; Guadagni, Veronica; Bettauer, Kaitlyn M.; Drogos, Lauren L.; Aitken, Julie; Hartmann, Sara E.; Furian, Michael; Muralt, Lara; Lichtblau, Mona; Bader, Patrick R.; Rawling, Jean M.; Protzner, Andrea B.; et al. (Frontiers in Physiology, 2018)
Objective: Neurocognitive functions are affected by high altitude, however the altitude effects of acclimatization and repeated exposures are unclear. We investigated the effects of acute, subacute and repeated exposure to 5,050 m on cognition among altitude-naïve participants compared to control subjects tested at low altitude. Methods: Twenty-one altitude-naïve individuals (25.3 ± 3.8 years, 13 females) were exposed to 5,050 m for 1 week (Cycle 1) and re-exposed after a week of rest at sea-level (Cycle 2). Baseline (BL, 520 m), acute (Day 1, HA1) and acclimatization (Day 6, HA6, 5,050 m) measurements were taken in both cycles. Seventeen control subjects (24.9 ± 2.6 years, 12 females) were tested over a similar period in Calgary, Canada (1,103 m). The Reaction Time (RTI), Attention Switching Task (AST), Rapid Visual Processing (RVP) and One Touch Stockings of Cambridge (OTS) tasks were administered and outcomes were expressed in milliseconds/frequencies. Lake Louise Score (LLS) and blood oxygen saturation (SpO2) were recorded. Results: In both cycles, no significant changes were found with acute exposure on the AST total score, mean latency and SD. Significant changes were found upon acclimatization solely in the altitude group, with improved AST Mean Latency [HA1 (588 ± 92) vs. HA6 (526 ± 91), p < 0.001] and Latency SD [HA1 (189 ± 86) vs. HA6 (135 ± 65), p < 0.001] compared to acute exposure, in Cycle 1. No significant differences were present in the control group. When entering Acute SpO2 (HA1-BL), Acclimatization SpO2 (HA6-BL) and LLS score as covariates for both cycles, the effects of acclimatization on AST outcomes disappeared indicating that the changes were partially explained by SpO2 and LLS. The changes in AST Mean Latency [ΔBL (−61.2 ± 70.2) vs. ΔHA6 (−28.0 ± 58), p = 0.005] and the changes in Latency SD [ΔBL (−28.4 ± 41.2) vs. ΔHA6 (−0.2235 ± 34.8), p = 0.007] across the two cycles were smaller with acclimatization. However, the percent changes did not differ between cycles. These results indicate independent effects of altitude across repeated exposures. Conclusions: Selective and sustained attention are impaired at altitude and improves with acclimatization.The observed changes are associated, in part, with AMS score and SpO2. The gains in cognition with acclimatization during a first exposure are not carried over to repeated exposures.